2020
DOI: 10.3390/molecules25132994
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Principles from Tamarix aphylla L.: A Bioassay-Guided Fractionation Study

Abstract: Natural products have served as primary remedies since ancient times due to their cultural acceptance and outstanding biodiversity. To investigate whether Tamarix aphylla L. modulates an inflammatory process, we carried out bioassay-guided isolation where the extracts and isolated compounds were tested for their modulatory effects on several inflammatory indicators, such as nitric oxide (NO), reactive oxygen species (ROS), proinflammatory cytokine; tumour necrosis factor (TNF-α), as well as the proliferation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Anti-inflammatory medications, both nonsteroidal and steroidal, are the most prescribed treatments. In most documented cases, the long-term use of these medicines is hampered by their side-effects, necessitating the therapeutic use of less toxic solutions with fewer unpleasant responses [ 62 , 63 ]. Consequently, there is a requirement for effective, safe, and cost-effective alternative therapies.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory medications, both nonsteroidal and steroidal, are the most prescribed treatments. In most documented cases, the long-term use of these medicines is hampered by their side-effects, necessitating the therapeutic use of less toxic solutions with fewer unpleasant responses [ 62 , 63 ]. Consequently, there is a requirement for effective, safe, and cost-effective alternative therapies.…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Furthermore, all mediators examined demonstrated inhibitory action in the presence of kaempferol. Therefore, T. aphylla constituents might be used as anti-inflammatory medications [ 63 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 99%
“…Our group's previous study revealed that owing to the presence of an abundant quantity of polyphenolic compounds in all four parts of TA extract and related species, they exhibited promising antioxidant activity by DPPH assay [ 25 , 30 ]. To support and validate the antioxidant potential of TA extracts, we evaluated the total antioxidant capacity (TAC) of all four TA extracts via phosphomolybdate assay.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of UPLC-QTOF-MS/MS Generally, we found that the phenolic compounds detected in the present study were also found in bamboo fruits of Melocanna baccifera [61], including cinnamic acid and syringic acid. Cinnamic acid is a phenolic compound naturally occurring in various vegetables, seeds, and also enriched in daily diets [62]. In addition, syringic acid is a phenolic compound that acts as a free radical scavenging antioxidant in pharmacology [63] and is rich in many edible mushrooms and vegetables and food and beverage plants [64].…”
Section: Identification Of Phenolic Compositionsmentioning
confidence: 99%